PERBEDAAN PRESTASI BELAJAR FISIKA DENGAN METODE DEMONSTRASI DAN EKSPERIMEN - Heri Poniman; Dwi Yulianti; I Dewa Putu Nyeneng (Indonesia Journal of Educational Technology, 2013)
This study aims to analyze: 1) differences in student achievement are given learning method and experimental demonstration, 2) differences in physics learning achievement of students who have high achievement motivation and low, 3) differences in physics learning achievement of students who have studied high and low activity , 4) the interaction between learning physics by using demonstrations and experiments with achievement motivation on academic achievement, 5) the interaction between learning physics demonstrations and experiments using this method with learning activities on student achievement, 6) interaction between achievement motivation with learning activity for achievement student learning, 7) the interaction between learning physics demonstrations and experiments using this method, achievement motivation and learning activities on student achievement.This research is a quasi-experiment using 2x2x2 factorial design. This study population is grade 7 SMPN 3 District Court in 2011, amounting to 5 classes. Sampling using random cluster sampling, the class 7A and 7E. Data obtained using questionnaires, tests and observation. Data analysis techniques using Analysis of Variance (ANOVA) three lines. The device used to process research data is Minitab 14, iteman program and excel.The results showed that: 1) there are differences in achievement by using the method of learning, experimental learning method gives better results than the methods of teaching demonstrations, 2) there is no difference in learning achievement of significant physics, the students have high achievement motivation and low , 3) there is a difference in student achievement, students with high learning activities earn higher returns than low learning activities, 4) there is no interaction between learning method with achievement motivation, 5) there is interaction between the method of learning with the learning activities, 6) are not there is an interaction between achievement motivation with learning activities on learning achievement, 7) there is no interaction between learning method, achievement motivation and learning activities on student achievement.Keywords: demonstrations, experiments, motivation